The Effect of Laughter Therapy on Reducing Anxiety Level in Hypertension Patients - Purnamasari, Erna; Andhiyani, Arvina (Journal for Quality in Public Health, 2021)
Degenerative diseases are chronic non-communicable diseases such as heart disease, hypertension, diabetes, obesity and others. One of the degenerative diseases is hypertension. Hypertension is referred to as the "Silent Killer" because it is a deadly disease, without any symptoms as a warning to sufferers. Concerns about the emergence of new problems in hypertension will cause emotional mental disorders which are often shown by anxiety disorders. One of the lifestyle modifications that can cope with hypertension is to recommend being more relaxed. One alternative for relaxation in patients with hypertension is laughter therapy. This study aims to determine the effect of laughter therapy on reducing anxiety levels in hypertension sufferers in the Work Area. Method research using Literature review related to the effect of laughter therapy on reducing anxiety level in Hypertension patient. The results of the normality of the data showed that the data were normally distributed in the intervention group and the data were not normally distributed in the control group. From the results of this study, it is hoped that laughter therapy can be given contribution to reduce anxiety levelsin hypertensive patients, so that blood pressure in hypertensive patients can be controlled.